ОСНОВИ ПРОФЕСІЙНОЇ ТВОРЧОСТІ МАЙБУТНЬОГО ВЧИТЕЛЯ (Педагогіка вищої та середньої школи, 2008)
The article deals with the pedagogical creative work as a showing of future teachers readiness for professional activity.